The Influence of Leadership, Organizational Commitment and Evaluation Monitoring on the Performance of Regional Apparatus Employees in Buleleng Regency - Desak Putu Suastini; Komang Krisna Heryanda; Ni Luh Wayan Sayang Telagawathi (Poltanesa, 2025)
This study aims to analyze the influence of leadership, organizational commitment, and evaluation monitoring on the performance of regional apparatus employees in Buleleng Regency. The quantitative method is used with a survey technique involving regional apparatus employees as respondents. The results of the study show that leadership plays an important role in improving employee performance through effective communication, work motivation, and the formulation of a clear vision. Organizational commitment has been proven to strengthen employee loyalty and responsibility, which has implications for increasing productivity and quality of public services. Evaluation monitoring plays a role in ensuring continuous performance improvement through the provision of constructive feedback and a more transparent accountability system. These three variables interact synergistically in creating a work environment that supports improving employee performance. This study makes a theoretical contribution by confirming the relationship between leadership, organizational commitment, and evaluation monitoring in the context of regional bureaucracy. Practically, the results of this research can be used as a basis for local governments in formulating strategic policies to improve the effectiveness of the work of the apparatus through strengthening leadership capacity, forming an adaptive organizational culture, and implementing a technology-based evaluation system. The recommendations of this study include the development of a more comprehensive leadership training program, the optimization of digital-based performance monitoring systems, and the increase of employee participation in the organizational decision-making process to strengthen their involvement in achieving the institution's goals.